The Modern Halaqah: Recontextualizing Bahtsul Masail Tradition as a Pedagogical Strategy for Critical Inquiry and Academic Excellence in Islamic Education Management - Abdul Halim; Faiz Faricha (https://journal.metanusantara.com/pedagogia, 2025)
The stagnation of academic culture in Islamic Higher Education (PTKI) demands a transformative intervention to shift the paradigm from passive learning to critical inquiry. This study analyzes the revitalization of academic culture through